Dekonstruksi Banking Education dalam Metode Hafalan Pesantren Komprehensif: Analisis Perspektif Pedagogy of the Oppressed di Pondok Pesantren Cipasung - Endang Komara; Ahmad Sukandar; Lelah Nurjamilah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to critically deconstruct the practical methods of memorizing (muhafadhah) the yellow books (kitab kuning) at Pondok Pesantren Cipasung, Tasikmalaya, through the sociocultural lens of Banking Education formulated by Paulo Freire. As a prototype of a comprehensive Islamic boarding school, Cipasung exhibits a highly dynamic pedagogical dualism: the endurance of salafiyah traditions that emphasize linear textual recitation, juxtaposed with a modern higher education academic landscape that demands critical thinking and scientific skepticism. Employing a qualitative-critical approach with a case study design, this research sharply unpacks how the structure of knowledge sedimentation operates within traditional circles and how student-ents (santri-mahasiswa) negotiate their critical consciousness under the hegemony of obedience doctrines. The sociocultural analysis demonstrates that the memorization method does not merely act as an instrument of pure intellectual oppression; rather, it functions as a cognitive infrastructure providing a database of religious texts. Nonetheless, this system poses a significant risk of perpetuating a frozen, naive consciousness if the post-memorization dialectical space remains closed by the dominance of the instructor’s sole authority. As a strategic solution, this study proposes a reconstruction model termed "Emancipatory Hybrid Dialectics," which integrates the strength of salaf textual recitation with the principles of problem-posing education to foster transformative critical consciousness in modern Islamic Education (PAI) learners.